Impact of Bifidobacterium animalis subsp. lactis HN019 probiotic in the prevention of periodontitis associated with immunosuppression - Maia, Luciana Prado (2023)
Background: This study evaluated the effects of the probiotic Bifidobacterium animalis subsp. lactis HN019 (HN019) in the development of experimental periodontitis (EP) in rats submitted to chemotherapy (5-fluorouracil [5FU]). Methods: Eighty male rats were divided into the following groups: control (C); treated with 5FU (60 mg/kg at day 30 and 40 mg/kg at day 32); treated with probiotic (HN019) (daily, for 44 days, starting at day 0); treatment with 5FU and probiotic (5FU-HN019); only EP (EP) (ligature placed on lower first molars at day 30, maintained for 14 days); EP and treatment with 5FU (EP-5FU); EP and treatment with probiotic (EP-HN019); and EP and treatment with 5FU and probiotic (EP-5FU-HN019). Euthanasia occurred at day 44. Morphometric, histomorphometric, microtomographic, immunohistochemical, immunoenzymatic, and gene expressions analyses were performed. The data obtained were statistically analyzed (p < 0.05). Results: The EP-5FU-HN019 group showed less bone and connective tissue loss when compared with EP-5FU group, while EP-HN019 and EP-5FU-HN019 groups had greater bone volume than EP and EP-5FU groups, respectively (p < 0.05). A decrease in immunostaining for tartrate-resistant acid phosphatase and RANKL, an increase for osteoprotegerin and lower interleukin-1β levels were observed in EP-5FU-HN019 group, when compared with EP-5FU group (p < 0.0001). Probiotic therapy led to an increase in the proportions of B. lactis in the feces (p = 0.0018), but not in the biofilm, and reduced the expression of Fusobacterium nucleatum and Prevotella intermedia in the biofilm (p < 0.0001). Conclusion: B. lactis HN019 reduced the severity of EP in rats submitted to chemotherapy, modulating immunoinflammatory parameters in periodontal tissues and reducing periodontopathogens expression on biofilm in rats submitted to chemotherapy.